CALCULATIONS OF (γ-n) REACTION CROSS-SECTION AND GAMMA RAY INCINERATION OF 144Ce, 144Nd, 151Sm AND 155Eu - Al-Bayati, Abdul-Hussain; Kamoon, Saeed; Saeed, Muna (Iraqi Journal of Science, 2024)
The evaluation of the (γ,n) cross section for radioactive fission products has been done in the present paper. The current research deals with heavy isotopes resulting from fission reactor, namely, 144Ce, 144Nd, 151Sm and 155Eu. The range of energy lays in the region of energy near the giant dipole resonance, from the threshold energy up to around 30 MeV. The present radioactive isotopes were chosen as part of the radioactive waste from 235U fission. Total cross section results then were found and calculated, and used to calculate the number of incinerated nuclei. By varying the gamma-ray fluxes and repeating the calculations, the present method shows efficiency in reducing the radioactivity of these isotopes. The results given in the present paper showed direct proportion between incinerated nuclei and the strength of the incident gamma-ray flux, which are consistent with earlier work.